2021
DOI: 10.1016/j.ymthe.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of ChAd63-KH vaccine in post-kala-azar dermal leishmaniasis patients in Sudan

Abstract: Post-kala-azar dermal leishmaniasis (PKDL) is a chronic, stigmatizing skin condition occurring frequently after apparent clinical cure from visceral leishmaniasis. Given an urgent need for new treatments, we conducted a phase IIa safety and immunogenicity trial of ChAd63-KH vaccine in Sudanese patients with persistent PKDL. LEISH2a (ClinicalTrials.gov: NCT02894008) was an open-label three-phase clinical trial involving sixteen adult and eight adolescent patients with persistent PKDL (median duration, 30 months… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…In addition to these clinical outcomes, we will also conduct in depth immune profiling using whole blood transcriptomics to evaluate vaccine-induced immunity and to determine whether there are biomarkers in blood that reflect either responsiveness to vaccine-induced cure or that predict self-cure. In our previously reported Phase 2a safety and immunogenicity study involving 24 patients 27 , we observed that immune modules associated with antigen presentation and macrophage function were significantly over-represented in patients that successful cleared their PKDL within 90 -120 days of vaccination. However, this study did not have a placebo control and so we were not able to determine whether these immune response differences were related to vaccine response or reflected patient heterogeneity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition to these clinical outcomes, we will also conduct in depth immune profiling using whole blood transcriptomics to evaluate vaccine-induced immunity and to determine whether there are biomarkers in blood that reflect either responsiveness to vaccine-induced cure or that predict self-cure. In our previously reported Phase 2a safety and immunogenicity study involving 24 patients 27 , we observed that immune modules associated with antigen presentation and macrophage function were significantly over-represented in patients that successful cleared their PKDL within 90 -120 days of vaccination. However, this study did not have a placebo control and so we were not able to determine whether these immune response differences were related to vaccine response or reflected patient heterogeneity.…”
Section: Discussionmentioning
confidence: 81%
“…Following external peer review of the data generated during LEISH1, a phase 2a study was funded in adults and adolescents with >six months PKDL. This trial successfully completed at the Dooka Centre for Tropical Medicine and the vaccine showed minimal adverse reactions in PKDL patients and induced potent innate and cell-mediated immune responses measured by whole-blood transcriptomics and ELISpot 27 .…”
Section: Rationale For a Therapeutic Cd8 + T Cell-inducing Vaccine Ag...mentioning
confidence: 99%
“…Immunochemotherapy may be second line treatment in chronic or refractory cases; the ChAd63-KH vaccine seems a suitable candidate to further build on previous experience with the autoclaved L. major vaccine ( Younis et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The phase IIa safety and immunogenicity trial was conducted in Sudanese patients with persistent PKDL. ChAd63-KH vaccine showed minimal adverse reactions and induced potent innate and cell-mediated immune responses [350].…”
Section: Third-generation Vaccinementioning
confidence: 99%